Smart Control and Monitoring System for Closed Poultry House based on IoT - Surateno, Surateno; Kautsar, Syamsiar; Rachmanita, Risse Entikaria; Anwaludin, Aan; Adhiyatma, M.; Hertawamati, Rosa Tri; Hariono, Budi; Purnomo, Fendik Eko; Sarena, Sryang Tera (Universitas Sanata Dharma, 2024)
The application of technology in the livestock sector has been carried out to increase the productivity of the livestock business. Closed chicken coops are one of the applications of technology in the livestock sector by utilizing a microcontroller that can control the temperature and ammonia levels in the coop under optimal conditions for fattening chickens. When the temperature rises (hot), the system set on the microcontroller will make the fan turn on automatically. This study aims to improve the offline and semi-manual fan control system in closed chicken coops to become automatic. By utilizing Internet of Things (IoT)-based technology, monitoring the condition of the chicken coop can be more easily accessed remotely. The method uses the if-then rule to regulate fan performance based on variable temperature and ammonia levels. The fan work set-point value can be set through the Android application online. Based on the test results, the IoT system treatment can work well. A consumer satisfaction survey was conducted on breeders with satisfactory results to ensure their feasibility as a commercial product.